The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0102-695x2012005000023
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperlipidemic activity of oryzanol, isolated from crude rice bran oil, on Triton WR-1339-induced acute hyperlipidemia in rats

Abstract: Experimental studies carried out for evaluating the anti-hyperlipidemic properties of rice bran components have given interesting but often contrasting results. Therefore, the current study was initiated to investigate the anti-hyperlipidemic activity of oryzanol (OZ), a commercially-important bioactive phytochemical, isolated from crude rice bran oil (cRBO). OZ was isolated by a two-step solvent crystallization process from cRBO, which was extracted from fresh rice bran by hexane mediated soxhlet extraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
(17 reference statements)
1
15
0
1
Order By: Relevance
“…In addition to those preliminary studies, other research has shown that there is a significant effect of these rice branderived products on improving the lipid profile (Table 6). However, black rice bran extracts reduce the progression of dietary cholesterolinduced atherosclerotic plaque development and cholesterol plasma levels in rabbits [125,126] while decreasing the levels of serum triglycerides and total cholesterol in mice [127].…”
Section: Hypocholesterolaemic Effects Of Rice By-productsmentioning
confidence: 99%
“…In addition to those preliminary studies, other research has shown that there is a significant effect of these rice branderived products on improving the lipid profile (Table 6). However, black rice bran extracts reduce the progression of dietary cholesterolinduced atherosclerotic plaque development and cholesterol plasma levels in rabbits [125,126] while decreasing the levels of serum triglycerides and total cholesterol in mice [127].…”
Section: Hypocholesterolaemic Effects Of Rice By-productsmentioning
confidence: 99%
“…In addition, a significant increase in the level of hepatic antioxidant enzymes showed a high degree of hepatic protection against free radicals. 38 γ-Oryzanol exerts a hypolipidemic effect even when blended with other vegetable oils. Rats fed a diet containing blends of refined groundnut oil having 3%, 5%, or 10% of γ-oryzanol showed a decrease in total cholesterol in serum (7-16%) and in liver (15%), depending on the γ-oryzanol concentration used, when compared to cholesterol levels of the rats fed on pure groundnut oil.…”
Section: Studies On Rbo and Its Components Against Dyslipidemiasmentioning
confidence: 99%
“…The isolation of OZ from cRBO using a modified two-step crystallization process previously described by Zullaikah et al (2009) has been discussed previously (Ghatak & Panchal, 2012a). The isolated OZ was identified with respect to the standard by melting point determination, thin-layer chromatography (TLC), UV-visible spectrophotometry and high-performance liquid chromatography (HPLC), the results of which have been published recently (Ghatak & Panchal, 2012b).…”
Section: Isolation Of Oz From Crbomentioning
confidence: 99%